Study on a catalytic membrane reactor for hydrogen production from ethanol steam reforming - Yua, C.Y.; Lee, D.W.; Park, S.J.; Lee, K.Y.; Lee, K.H.
Ethanol steam reforming in a membrane reactor with catalytic membranes was investigated to achieve important aims in one process, such as improvement in ethanol conversion and hydrogen yield, high hydrogen recovery and CO reduction. In order to confirm the efficiency of reaction and CO reduction, an ethanol reforming-catalytic membrane reactor with water-gas shift reaction (ECRW)in the permeate side was compared with a conventional reactor (CR)and an ethanol reforming-catalytic membrane reactor (ECR). In comparison with the CR, ethanol conversion improvement of 11.9-19
Keywords: HYDROGEN PRODUCTION; ETHANOL STEAM REFORMING; MEMBRANE REACTOR; CATALYTIC MEMBRANES; WATER-GAS SHIFT REACTION